2022
DOI: 10.3389/fphar.2022.956173
|View full text |Cite
|
Sign up to set email alerts
|

Traditional chinese medicine to prevent and treat diabetic erectile dysfunction

Abstract: Diabetic erectile dysfunction (DED) is one of the most common complications of diabetes mellitus. However, current therapeutics have no satisfactory effect on DED. In recent years, traditional Chinese medicine (TCM) has shown good effects against DED. By now, several clinical trials have been conducted to study the effect of TCM in treating DED; yet, the underlying mechanism is not fully investigated. Therefore, in this review, we briefly summarized the pathophysiological mechanism of DED and reviewed the publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…Preclinical trials indicated that TCM could improve erectile function by suppressing oxidative stress, curing vascular endothelial injury, inhibiting apoptosis, and anti-atherosclerotic effects. [25][26][27][28] Further research validates that TCM combined with tadalafil has significant efficacy in treating ED with no increase in side effects. 29 Accumulating research focuses on the efficacy of TCM on ED and a systematic evaluation of whether TCM is available as a complementary and alternative therapy is in need.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Preclinical trials indicated that TCM could improve erectile function by suppressing oxidative stress, curing vascular endothelial injury, inhibiting apoptosis, and anti-atherosclerotic effects. [25][26][27][28] Further research validates that TCM combined with tadalafil has significant efficacy in treating ED with no increase in side effects. 29 Accumulating research focuses on the efficacy of TCM on ED and a systematic evaluation of whether TCM is available as a complementary and alternative therapy is in need.…”
Section: Introductionmentioning
confidence: 77%
“…Formal research has assessed the effectiveness and safety of acupuncture for ED 24 ; thus, the current study focused on the oral application of Chinese herbal medicine. Preclinical trials indicated that TCM could improve erectile function by suppressing oxidative stress, curing vascular endothelial injury, inhibiting apoptosis, and anti‐atherosclerotic effects 25–28 . Further research validates that TCM combined with tadalafil has significant efficacy in treating ED with no increase in side effects 29 .…”
Section: Introductionmentioning
confidence: 88%
“…Quanzhenyiqitang (QZYQT) is a traditional Chinese formula that was first listed in the book “Feng Shi Jin Nang Mi Lv” written by Fengzhaozhang in the Qing dynasty. QZYQT is composed of seven traditional Chinese herbs, including Shudi ( Rehmanniae Radix Praeparata ), Dangshen ( Codonopsis Radix ), Maidong ( Ophiopogon Radix ), Baizhu ( Atractylodes Macrocephala Rhizoma ), Niuxi ( Achyranthes Bidentata Radix ), Fuzi ( Aconiti Lateralis Radix Praeparata ), and Wuweizi ( Schisandra Chinensis Fructus ) [5] . QZYQT is used clinically to treat asthma and chronic obstructive pulmonary disease (COPD) in China [6] .…”
Section: Introductionmentioning
confidence: 99%
“…QZYQT is composed of seven traditional Chinese herbs, including Shudi (Rehmanniae Radix Praeparata), Dangshen (Codonopsis Radix), Maidong (Ophiopogon Radix), Baizhu (Atractylodes Macrocephala Rhizoma), Niuxi (Achyranthes Bidentata Radix), Fuzi (Aconiti Lateralis Radix Praeparata), and Wuweizi (Schisandra Chinensis Fructus). [5] QZYQT is used clinically to treat asthma and chronic obstructive pulmonary disease (COPD) in China. [6] Previous studies have shown that QZYQT can attenuate lung inflammation and oxidative stress in mice exposed to tobacco smoke.…”
Section: Introductionmentioning
confidence: 99%